Elaboración de compota de mamey colorado (Colocarpum mammosum toxón) y mamey cartagena (Mammea americana toxón L), en el cantón Quevedo. - Coello Fernández, Néstor Roberto (2017)
The cultivation of mamey in Ecuador is considered as a fruit of good taste, with high nutritional and medicinal properties. However, its use is not very conventional, so various institutions seek to promote the supply of non-traditional products, achieving economic insertion at an international level with products made from this raw material. The objective of this work was to evaluate and compare the effect of different treatments (sugar levels and two varieties of mamey) on the chemical, microbiological and sensorial physical stability of the fruit pulp of mamey colorado (Colocarpum mammosum) and mamey cartagena (Mammea americana) for composting. For the effect, a completely randomized design was used, with a 2 x 3 factorial arrangement, with three replicates. Tukey's test was used to compare the means of treatment (p≤0.05). For the development of the compotes the pulp of mamey is used as raw material, using experimental tests to determine the sensorial, physical-chemical and microbiological quality. The study showed that the response variables: pH and titratable acidity, varied significantly (p ≤ 0.05) during storage, as compared to total soluble solids whose changes were not considered statistically significant. The concentration of ascorbic acid during storage showed different degradation rates, proving that suitable thermal treatments provoke positive effects in the samples, being this an important characteristic in the elaboration of any product destined to the human feeding.